The Influence of Compensation on Organizational Citizenship Behavior: The Mediating Role of Work Motivation - Setiawan, Ainur Rahim; Wahyuni, Aria Dian Tri; Widjaja, Ratna A Marhaenita; Irianti, Rosi; Kuswandono, Andi (⁠International Journal of Sustainable Social Culture, Science Technology, Management, and Law Humanities, 2025)
This study aims to examine the effect of compensation on Organizational Citizenship Behavior (OCB), with work motivation as a mediating variable. Using a quantitative explanatory research approach, data were collected from 120 permanent employees of a logistics company through questionnaires and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings show that compensation has a positive and significant effect on both work motivation and OCB. Furthermore, work motivation also significantly influences OCB and mediates the relationship between compensation and OCB. These results suggest that fair and competitive compensation not only directly encourages employees to exhibit extra-role behaviors, but also indirectly enhances OCB by increasing work motivation. This study emphasizes the importance of integrating compensation strategies with psychological factors such as motivation to foster a more engaged and committed workforce. The research contributes both theoretically and practically to human resource management by highlighting motivation as a critical link in the compensation OCB relationship.